Analisis Faktor Ergonomi Terhadap Kinerja Pekerja Las (Studi Kasus Pekerja Las di Daerah Surakarta) - Wisudawati, Tri; Putera, Radita Dwi; Sastyawan, Ragil (Fakultas Teknik Universitas Tulang Bawang, 2025)
Human resources are one of the factors that influence the progress of the business being undertaken. The Surakarta area has an increasing number of MSMEs every year. One of the MSMEs that is growing is a welding workshop. There are several things that affect employee performance, one of which is ergonomic conditions. Of course, this condition can be described in the task or work factor that is assigned. This study aims to analyze ergonomic factors on the performance of welding workers in the Surakarta area. The research method used is descriptive qualitative. The number of respondents or samples in this study was 50 welding workers in the Surakarta area. The data analysis method used is Structural Equation Modeling (SEM). The work environment around the welding workshop actually affects employee performance. One of them is ergonomics. The ergonomic aspect of performance is influenced by several factors, two of which are work organization and workload. This study uses work organization and workload variables as indicators of measuring ergonomic factors on the performance of welding workers in the welding workshop. Based on the results of the study, it can be seen that the work organization variable as an ergonomic indicator has a positive influence on the performance of workers in the welding workshop. This can be seen from the p values ​​of 0.000 less than the alpha value of 5%. There are three aspects that can optimize employee performance in terms of work organization, namely effective communication between fellow workers, good human resource management and optimal work time task design. Meanwhile, the performance load does not affect the performance of welding workers in the welding Keywords: Ergonomics, Surakarta, Welding, Workers